The challenge of the future : future trends in adult and continuing technical and vocational education. An international symposium - Mishra, Arun K. [Mitarbeiter]; Kumar, Ajit [Mitarbeiter]; Foster, Helga [Mitarbeiter]; Olesen, Henning Salling [Mitarbeiter]; Ntomambanga Ningo, Ndeh [Mitarbeiter]; Belanger, Paul [Mitarbeiter]; Castro, Aker Aragon [Mitarbeiter]; Munbodh, Suresh [Mitarbeiter]; Bogantes, Fernando [Mitarbeiter]; Hinchcliff, John C. [Mitarbeiter]; Peshkov, S.I. [Mitarbeiter] (UNESCOS's UNEVOC Implementation Unit, 1996)
Der Band stellt Einzelbeiträge und die zentralen Themen der Diskussion eines Symposiums der UNESCO zur zukünftigen Entwicklung der Weiterbildung zusammen. Folgende Beiträge sind enthalten: MISHRA/KUMAR: Adult and continuing technical and vocational education in India; FOSTER: The contribution of technical and vocational education to the opening up of careers for women; OLESEN: The change and impact of culture on the worker and on work; NTOMAMBANG NINGO: The changing provision and participation patterns in adult and continuing technical and vocational education; BELANGER: Adult learning and the transformation of work; CASTRO: The changes in the content and educational approaches; MUNBODH: The changing orientation and policy environment of adult and continuing technical an vocational education; BOGANTES: The transformation of work in the different regional contexts; HINCHCLIFF: The "tossed salad" approach to cultural identity in the contemporary workplace; PESHKOV: ICES activity in consolidation of international, governmental and non- governmental actors for adult and continuing education. (BIBB)
Keywords: G 2.2.4 Lebensbegleitendes & lebenslanges Lernen; L 1 Curricula & Lehrpläne; L Lehren & Lernen; G 1.2 Arbeitsmarkt; G 2.3.5 Wirtschaftsstrukturwandel; I 2.3.4 Asien; I 2.2.1 Westeuropa; I 2.3.3 Lateinamerika; I 2.3.2 Nordamerika; I 2.2.2 Osteuropa; Erwachsenenbildung; Lebenslanges Lernen; Berufliche Weiterbildung; Arbeitswelt; Strukturwandel; Lerninhalt; Lernziel; Zielgruppe; Frauen; Indien; Dänemark; Kamerun; Frankreich; Kuba; Mauritius; Costa Rica; USA; Russland